2000
DOI: 10.1007/s001250050022
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and vascular responses in Type I diabetes

Abstract: Diabetic microangiopathy and macroangiopathy are the principal causes of morbidity and mortality in patients with diabetes mellitus [1±3]. Patients with Type I (insulin-dependent) diabetes mellitus have a three to sixfold increased risk of cardiovascular death before the age of 60 compared with non-diabetic subjects [4]. Established risk factors for coronary heart disease (CHD) do not, however, fully explain the increased risk in Type I diabetic patients [5].The vascular endothelium has a key role in maintaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 119 publications
6
68
0
2
Order By: Relevance
“…Hyperglycemia could induce increased NO production and reduced NO availability due to inactivation, mediated by free radicals. Recent work suggests that in type 1 diabetes, there could be specific defects in signal transduction mechanisms linked to NO synthase (receptors, ion channels), NO synthase expression, or destruction of NO after it has been produced (36). Skin biopsies from the dorsum of the foot of patients with diabetes have also shown a significant decrease in endothelial NO synthase expression, and this may prove to be the potential cause of reduced endothelial function (29,37).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia could induce increased NO production and reduced NO availability due to inactivation, mediated by free radicals. Recent work suggests that in type 1 diabetes, there could be specific defects in signal transduction mechanisms linked to NO synthase (receptors, ion channels), NO synthase expression, or destruction of NO after it has been produced (36). Skin biopsies from the dorsum of the foot of patients with diabetes have also shown a significant decrease in endothelial NO synthase expression, and this may prove to be the potential cause of reduced endothelial function (29,37).…”
Section: Discussionmentioning
confidence: 99%
“…mental model of diabetes in the rabbit Chan et al, 2000 . It is generally accepted that endothelium-dependent relaxation is impaired in different vascular beds of several animal species with experimentally induced diabetes mellitus, whereas this endothelium-mediated vasodilatation also Ž appears impaired or unchanged in diabetic patients see, . for review, Sobrevia and Mann, 1997;Chan et al, 2000 . However, there are some reports that show an enhanced endothelium-dependent relaxation in response to histamine Ž . Ž White andCarrier, 1986 andto acetylcholine Bhardwaj .…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological processes underlying vascular complications are still poorly understood. However, in recent years, several lines of evidence have suggested that some of the vascular changes in diabetes may be related to alterations in en-Ž dothelial function see, for review, Chan et al, 2000;De . Vriese et al, 2000 . Endothelial cells are known to play a central role in the regulation of vascular tone both in physiological and pathophysiological conditions through the release of differ-ent vasodilator and vasoconstrictor substances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, these drugs decrease the risk of vascular events in patients with cardiovascular disease and ischemic stroke irrespective of the baseline LDL-C level 6) . The maintenance of physiological vascular tone and structure depends on endothelial production and the release of nitric oxide (NO) 7) . Asymmetric dimethylarginine (ADMA) was recently characterized as an endogenous, competitive inhibitor of NO synthase and is now considered a novel independent risk factor for endothelial dysfunction 8) .…”
Section: Introductionmentioning
confidence: 99%